DEVELOPMENT OF A TOPICAL GEL CONTAINING A DIPEPTIDYL PEPTIDASE-4 INHIBITOR FOR WOUND HEALING APPLICATIONS: 16th August 2022; 11th January 2023; 22nd February 2023; 06th March 2023 - Pokrathok, Phawini; Muangman, Pornprom; Namviriyachote, Nantaporn; Viravaidya-Pasuwat, Kwanchanok (MATTER: International Journal of Science and Technology, 2023)
Chronic wounds are challenging for healthcare because they are difficult to treat and cannot heal by themselves. Active compounds that can accelerate wound healing are, therefore, necessary. Dipeptidyl peptidase (DPP)-4 inhibitors are antihyperglycemic drugs widely used in patients with type 2 diabetes that not only maintain the homeostasis of blood sugar levels but have also been shown to promote chronic wound healing. In this study, we formulated a topical gel containing, sitagliptin, a commonly used DPP-4 inhibitor drug to treat diabetes, using Carbopol 940 as a base due to its high viscosity and biocompatibility. The characteristics of the sitagliptin gel, including its physical appearance, viscoelastic properties, swelling and degradation, and stability, were investigated. The gel appeared to be transparent with a uniform distribution of drug molecules and was stable at 4 °C for more than 1 month. Moreover, the gel was shown to exhibit shear thinning pseudoplastic behavior, which is desirable for topical gels. The gel could absorb up to 250% of liquid within 2 days but later degraded in aqueous solution following zeroth-order kinetics. In the in vitro release study, the cumulative release data were best fitted with the first order kinetic model, in which the release rate depended on the concentration. To further demonstrate the use of the DPP-4 inhibitor gel, the gel was applied directly onto subcutaneous wounds on experimental pigs. The topical gel was shown to exhibit the desired spread ability without causing any inflammation around the wound area which was comparable to IntraSite® gel and commercial silver nanoparticle cream.